2001
DOI: 10.2165/00007256-200131080-00003
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Leptin and Exercise

Abstract: The cloning of murine and human obese genes in 1994, and the subsequent identification that the product of the obese gene, leptin, is secreted from adipose tissue, stimulated a tremendous amount of interdisciplinary interest in adipose tissue endocrinology and the potential role of this tissue in the regulation of energy balance. Exercise, with concomitant changes in fuel flux, systemic hormone levels and energy expenditure, may contribute to the regulation of plasma leptin levels and presumably, leptin action… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
2

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 56 publications
3
26
2
Order By: Relevance
“…Recent studies have provided the most compelling evidence to date of the interaction between exercise, energy balance and systemic leptin in humans [25]. In the present study, there was a negative correlation between physical activity and energy balance (r = –0.60, p < 0.01) probably due to its positive correlation with energy expenditure (r = 0.80, p < 0.001).…”
Section: Discussionsupporting
confidence: 46%
“…Recent studies have provided the most compelling evidence to date of the interaction between exercise, energy balance and systemic leptin in humans [25]. In the present study, there was a negative correlation between physical activity and energy balance (r = –0.60, p < 0.01) probably due to its positive correlation with energy expenditure (r = 0.80, p < 0.001).…”
Section: Discussionsupporting
confidence: 46%
“…However, it may be not a good indicator under an unstable state (Hickey & Calsbeek 2001). In the present study, there was a positive relationship between serum leptin levels and body fat mass in the control group, but no obvious tendency in the exercise-trained group.…”
Section: Body Mass Body Fat Mass and Serum Leptin Levelscontrasting
confidence: 60%
“…In humans, the systemic leptin level has been reported to be proportional to the body fat mass [2, 3]. In trained subjects, the circulating leptin level is low, and even at biologically extremely low levels of body fat, the leptin concentration is closely related to the body fat content in male athletes [3, 4]. …”
Section: Introductionmentioning
confidence: 99%
“…An exercise-mediated negative energy balance may contribute to the regulation of plasma leptin levels and presumably leptin action [3, 4]. Furthermore, it has recently been suggested that the regulation of leptin may also depend on factors at the metabolic level associated with certain long-term exercise regimens [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation